Otimização da degradação da tetraciclina utilizando a fotocatálise heterogênea com ZnO como catalisador - Davis, Rafael (2013)
The aim of this work was to determine the optimal conditions for the degradation of the TC, using the heterogeneous phtocatalysis with ZnO catalyst. Preliminary experiments were conducted to evaluate to efficiency of heterogeneous photocatalysis in the degradation of TC. The degradation was carried out using standard solutions of TC 30 mg L 1. The photocatalytic experiments by using a set of high-pressure mercury lamps as artificial UV irradiation source were performed in laboratory scale. As reactor operational parameters to be optimized by a 33 full factorial experimental design: hydrogen peroxide and zinc oxide as well as the initial solution pH were chosen as variables, keeping constant a reaction time of 60 min. The concentration of TC was determined by UV-Vis spectrophotometry and HPLC. Mineralization and toxicity of the treated solution by photocatalytic process were evaluated based on the total organic carbon (TOC) and antibacterial activity. Second-degree models for the degradation of TC were proposed to model the photocatalytic experiments to obtain optimum values of the reactor operating parameters. Second-degree models were also validated by ANOVA. Predicted yields showed good validation with experimental yields. The hydrogen peroxide did not influence significantly the range studied by factorial experimental design. Was necessary to perform photocatalytic experiments at lower concentrations for hydrogen peroxide. The values of the optimized reactor operational parameters were 6, 2 g L-1 and 175 mg L-1 for initial pH, oxide zinc and hydrogen peroxide concentrations, respectively, for photocatalyses heterogeneous process. Based on this optimized experimental conditions, almost 100% of TC degraded. The TOC and antibacterial activity were determined of treated solutions in optimal conditions. Only 46% of the TOC was mineralized, the remainder as intermediate molecules not presented antibacterial activity, not providing risk to the environment.